Soil microbial community parameters affected by microplastics and other plastic residues - Li, Yüze; Hou, Yuting; Hou, Quanming; Long, Mei; Wang, Ziting; Rillig, Matthias C.; Liao, Yuncheng; Yong, Taiwen (Frontiers in Microbiology, 2023)
Introduction: The impact of plastics on terrestrial ecosystems is receiving increasing attention.Although of great importance to soil biogeochemical processes, how plastics influence soil microbes have yet to be systematically studied. The primary objectives of this study are to evaluate whether plastics lead to divergent responses of soil microbial community parameters, and explore the potential driving factors.Methods: We performed a meta-analysis of 710 paired observations from 48 published articles to quantify the impact of plastic on the diversity, biomass, and functionality of soil microbial communities.Results and Discussion: This study indicated that plastics accelerated soil organic carbon loss (effect size = -0.05, p = 0.004) and increased microbial functionality (effect size = 0.04, p = 0.003), but also reduced microbial biomass (effect size = -0.07, p < 0.001) and the stability of co-occurrence networks. Polyethylene significantly reduced microbial richness (effect size = -0.07, p < 0.001) while polypropylene significantly increased it (effect size = 0.17, p < 0.001). Degradable plastics always had an insignificant effect on the microbial community. The effect of the plastic amount on microbial functionality followed the "hormetic dose-response" model, the infection point was about 40 g/kg. Approximately 3564.78 μm was the size of the plastic at which the response of microbial functionality changed from positive to negative. Changes in soil pH, soil organic carbon, and total nitrogen were significantly positively correlated with soil microbial functionality, biomass, and richness (R 2 = 0.04 -0.73, p < 0.05). The changes in microbial diversity were decoupled from microbial community structure and functionality. We emphasize the negative impacts of plastics on soil microbial communities such as microbial abundance, essential to reducing the risk of ecological 3 surprise in terrestrial ecosystems. Our comprehensive assessment of plastics on soil microbial community parameters deepens the understanding of environmental impacts and ecological risks from this emerging pollution.